Botanical comparison study on the wood pastures of Cserépfalu and Erdőbénye - Saláta, Dénes; Wichmann, Barna; Házi, Judit; Falusi, Eszter; Penksza, Károly (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
In this case we studied the grazed grassland and grassland complex vegetation of Cserépfalu’s (Bükk Moutain Range) and Erdőbénye’s (Tokaj–Zemplén Mountain Range) wood pastures in the North Hungarian Mountains. The coenological survey was made in the June of 2011 based on the method of Braun-Blanquet (1964) with 2×2 meters sampling quadrats. The areas were separated different zones as woody-scrub-grasslands ‘wood pasture’ (W) and grassland (G) zones. In the zones we separately studied the intensively grazed (A), less intensively grazed (B) and abandoned (C) parts. 135 species were found in the examined zones. The presence of 61 species is independent from zones or areas. 44 is the number of the species were found only at Cserépfalu and 17 were found only at Erdőbénye. 9 is the number of the species were found in only the zone of wood pastures (B) and 4 were found only in the open grasslands. The woody-scrub-grassland complexes were similar from the side of species composition and diversity, but this similarity is not depending from the location of investigated areas. The species stock was higher in the case of grazed areas and mainly in the case of spare grazed zones, so the management benefits can better materialize in parallel with the keeping of conservational values in this situation.